Computational Modelling of Two Terminal CIGS/Perovskite Tandem Solar Cells with Power Conversion Efficiency of 23.1 %. Issue 47 (11th May 2021) - Kumar, Anjan; Singh, Sangeeta; Mohammed, Mustafa K. A.; Shalan, Ahmed Esmail
Abstract: An appealing and feasible approach to develop an ultra‐high performance and price‐effective all‐thin‐film photovoltaic cell is to use a perovskite and copper indium gallium selenide (CIGS) in tandem configuration. In this simulation‐based study, an innovative 2‐terminal (2T) perovskite‐CIGS tandem solar cell has been proposed with extended cost savings, along with improved performance. First, a perovskite top cell with a bandgap of 1.5 eV and CIGS bottom subcell with 1.1 eV bandgap are simulated to have conversion efficiency of 16.69 and 15.98 %, respectively. The systems are tested for tandem configuration after setting the individual top and bottom subcells to correct values. To calculate the current matching point, both top and bottom absorber layer thicknesses are varied. The optimised thicknesses are 151 and 1000 nm for top and bottom subcells in the tandem cells. The top cell performance parameters are calculated by illuminating standard AM 1.5G solar spectrum keeping absorber thickness at 151 nm. While as, the bottom cell performance parameters are estimated using illumination of the filtered spectrum. The proposed tandem configuration composed of CIGS/CdS/ZnO/Spiro/Perovskite/C‐TiO2 showed a power conversion efficiency and open‐circuit voltage of 23.17 % and 1.646 volts, respectively. Consequently, we consider that the current study would deliver considerable progression in the field of CIGS/perovskite tandem photovoltaic cells, toward commercial applications. Abstract : An innovative 2‐terminal (2T) perovskite‐CIGS tandem solar cell has been proposed with extended cost savings, along with improved performance of 23.1 %. First, a perovskite top cell with a bandgap of 1.5 eV and CIGS bottom subcell with 1.1 eV bandgap are simulated to have conversion efficiency of 16.69 and 15.98 %, respectively.